Sequential and nonsequential monte carlo in assessing reliability performance of distribution network - Nur Nabihah Rusyda, Roslan; NoorFatin Farhanie, Mohd Fauzi; Mohd Ikhwan, Muhammad Ridzuan (Institute of Electrical and Electronics Engineers Inc., 2020)
Reliability evaluation is one of the fundamental methods in determining the stability of the distribution network. The variety of techniques in evaluating the reliability has increased as time passes, and the development of the distribution system also becomes more complex. Any network once it is starting to operate, the time for the network to fail, increases as the time passes, mostly when operated for a long time. Hence, it becomes a questionable situation whether the network will keep functioning without any fault or else there will be faults that occur between the operation times. Thus, due to that, the reliability evaluation was used to estimate the reliability of the network. Hence, based on the current evaluation methods, which methods suitable to evaluate the distribution networks without neglecting the distribution network's complexity. Two methods were used: Sequential Monte Carlo (SMC) and Nonsequential Monte Carlo (NSMC). These two methods are used to determine the efficiency of output and to check whether both methods suitable to apply for the current distribution system. IEEE-14 buses are used to simulate the reliability of the network and the efficiency of reliability output. It is expected both methods produce almost the same result. Based on the output, the values for the reliability indices (SAIFI, SAIDI, CAIDI) for this simulation are different due to the simulation process. Practically based on the output, it shows that the SMC method is more suitable to evaluate the distribution system since it pictures the real situation because of the time-based simulation.